Restoring subsoil degradation with mixed fertilizer-conditioner: A case study on red chili pepper (Capsicum annuum) cultivation - Stefina Liana Sari; Nguyen Quoc Khuong; Emma Trinurani Sofyan; Saefur Rohman; Rahmat Budiarto; Eso Solihin (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2025)
The loss of topsoil in high-rainfall regions significantly reduces agricultural productivity, especially in degraded soils. This study investigated the effects of Mixed Fertilizer-Conditioner (MFC) on improving the chemical properties of subsoil cultivated with red chili peppers. A Randomized Block Design (RBD) with 11 treatments on subsoil and one control on normal soil was implemented, with three replications. The treatments included: A= subsoil without fertilizer, B= 0% MFC + full NPK, C= 25% MFC + full NPK, D= 50% MFC + full NPK, E= 75% MFC + full NPK, F= 100% MFC + full NPK, G= 50% MFC + 75% NPK, H= 50% MFC + 50% NPK, I= 50% MFC + 25% NPK, J= 50% MFC without NPK, and K= Full NPK on normal soil. The application of 100% MFC combined with full NPK significantly enhanced subsoil chemical properties. Soil organic carbon increased to 1.32%, pH rose to 6.3, CEC reached 22.1 cmol kg⁻¹, and base saturation improved to 49.4%. Nutrient availability also increased, including total N (1.21%), P (0.132%), K (0.677 cmol kg⁻¹), along with Ca (1362.72 ppm), Mg (311.04 ppm), and S (36.01 ppm). Micronutrients B, Co, and Zn also rose to 4.41 ppm, 18.95 ppm, and 11.97 ppm, respectively. Chili yields in subsoil treated with 50–100% MFC and full NPK exceeded 10 tons ha⁻¹. These results highlight the agronomic potential of MFC for rehabilitating degraded soils and recommend its use as a sustainable strategy to enhance soil fertility in low-fertility or erosion-prone areas, with implications for both farmers and agricultural policymakers.